Curettage combined with bone cavity opening reduces recurrence of the mandibular conventional ameloblastoma and effectively preserves the mandible: a retrospective study - Yuan Zhang; Aili Xing; Jingya He; Feng Wang; Zhongrui Li; Bin Sun (BMC, 2023)
Abstract Background Patients with mandibular conventional ameloblastoma undergoing radical surgical treatment experience greater trauma and often find it challenging to accept, whereas conservative therapy is associated with a higher recurrence rate. In this study, we have improved traditional conservative treatment for mandibular conventional ameloblastoma by curettage combined with bone cavity opening (Cur/BCO). This retrospective study aimed to evaluate the effectiveness of the Cur/BCO treatment by comparing its recurrence rate and bone mineral density (BMD) growth rate with the traditional conservative treatment approach. Methods A total of 40 patients, meeting the study's inclusion and exclusion criteria from 2012 to 2020, were screened, with 20 in the modified group and 20 in the traditional group. ImageJ (RRID: SCR_003070) software was employed for measuring image indices. All data were analyzed using T-test, Chi-square test and Fisher exact test in SPSS 26.0 (p = 0.05). Results The incidence of recurrence was significantly lower in the modified group, at only 5%, compared to 35% in the traditional group (p < 0.05). Regarding bone mineral density (BMD) growth rate, the average value in the modified group was 0.0862 ± 0.2302 (/month), significantly higher than the average value of 0.0608 ± 0.2474 (/month) in the traditional group (p < 0.05). Conclusions In this study, it was found that the recurrence rate of the modified conservative treatment (Cur/BCO) was lower than that of the traditional conservative treatment for managing mandibular conventional ameloblastoma. Furthermore, the BMD growth rate was quicker in the modified group. Thus, Cur/BCO could be considered as a viable option for the conservative treatment of mandibular conventional ameloblastoma.